Ortogonblender: guia prático para o uso do software livre na cirurgia ortognática - Souza, Marianna Matos (2018)
This work aims to present the functionalities of the OrtogOnBlender add-on - a complement of the open source software Blender - for the virtual planning of orthognathic surgeries. The visualization, manipulation and creation of three-dimensional objects (3D) by computational means offered the buco-maxillofacial surgeon the opportunity to 1) plan surgeries with virtual models, 2) manufacture surgical guides based on the concept of computer-aided design / aided manufacturing (CAD / CAM) and 3)estimate three-dimensional postoperative outcomes, facilitating surgical choices and communication with patients. Despite the advantages of virtual planning in orthognathic surgery and implantodontics, the software used for this purpose is usually closed source, high cost and offers relatively limited resources regarding the customization of osteotomies and the alternation between functionalities (orthognathic module vs. implantodontia module, for example). Although Blender's native tools - a free graphic animation software based on the Python computational language - are designed for computer graphics projects, the OrtogOnBlender add-on has been developed in a collaborative way and enables 1) the conversion of DICOM files to virtual structures models 3D, 2) the creation of a textured 3D object that mimics the face of the patient by photogrammetry, 3) the realization of customizable virtual osteotomies by means of Boolean calculations, 4) the manipulation of the osteotomized segments according to the facial analysis performed by the surgeon , 5) visualization of surgical results in a three-dimensional and textured way, and 6) creation and preparation of surgical guides for 3D printing. Conclusion: The OrtogOnBlender add-on offers buco-maxillofacial surgeons a virtual planning tool in viable orthognathic surgery, inexpensive and user-customizable, features that favor its use by a broader base of users that promotes, therefore, its continued growth and evolution, as well as its possible application in the Unified Health System.